PENGARUH PERCEIVED QUALITY TERHADAP KESETIAN MEREK DAN CITRA MEREK - Wisnu Wisnu; Asep Hermawan (Jurnal Manajemen dan Pemasaran Jasa, 2011)
The aims of this research is to explore interrelation of perceived quality toward brand loyalty and brand image in hotel industry. The research is based on recommendation of previous studies, the scale constructed to measure perceived quality, brand loyalty and brand image. The present study used sample of selected 100 actual guest of GrandTropic Suites Hotel Jakarta. Multiple Regression is used to test the model.The Findings in this research support the brand loyalty and brand image in hotel industry. The present study contributes to the understanding of customer-based brand loyalty and brand imageby examining the dimensionality of this construct. Further research should attempt to examine and compare brand loyalty and brand image among different hotel categories. The research shows that hotel managers should try to influence perceived quality, brand loyalty and brand image in their organization and design their service delivery process by considering relations between customer based brand loyaltyand brand image.Keywords: Hotel, Perceived Quality, Brand Loyalty, Brand Image.